Facilely fabricated Dy:PbI2/glass thin films and their structural, linear and nonlinear optical studies for opto-nonlinear applications. (March 2020) - Shkir, Mohd; Khan, Aslam; Ansari, Anees A.; El-Toni, Ahmed Mohamed; Yahia, I.S.; Khan, M. Ajmal; Algarni, H.; AlFaify, S.
Abstract: The fabrication of Dy:PbI2 /glass (Dy = 0.0 to 0.8 wt%) films were performed using a spin coating process. X-ray diffraction confirmed the formation of monophasic hexagonal films growth along (001) planes. The estimated size of crystallites was noticed to be in the range of 16–22 nm. Scanning electron microscopy (SEM) study indicates the strong effect of Dy content on the morphology of film surface and the grown grain sizes were in 13–70 nm range. EDX/SEM e-mapping approves the existence of Dy in PbI2 films. The transparency of grown films was found to be in the range of 60 to 87%. Optical bandgap was estimated to be 2.21 eV–2.35 eV range. The values of index of refraction was found in 2–8 range. The constant of dielectric values was noted in the range of 5–50 and showed an enhancement by Dy doping. The value of χ (1) was noticed to be increased by Dy content doping and found in the range of 0.2–7. The χ (3) values were calculated in the range of 3.4 × 10 −1 3 to 3800 × 10 −10 esu. The n 2 values were noted to be in the range of 6 × 10 −12 to 1.5 × 10 −6 esu. The remarkable enhancement on nonlinear values proposed the grown Dy:PbI2 /glass films for opto-nonlinear applications. Highlights: Nanostructured thin films of Dy:PbI2 /glass has been low-costly fabricated for the first time. Mono-phase and high crystallinity of films was approved by XRD/Raman analysis. SEM study revealed low dimension nanoparticles formation. The optical band gap was calculated to be in range of 2.21 eV to 2.35 eV. An increase in χ(3) values were observed from 5 × 10 −10 to 4000 × 10 −10 esu.